2010
DOI: 10.1086/649966
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Bile Salts in Fish and Amphibians: Evolution of a Complex Biochemical Pathway

Abstract: Bile salts are the major end-metabolites of cholesterol and are also important in lipid and protein digestion, as well as shaping of the gut microflora. Previous studies had demonstrated variation of bile salt structures across vertebrate species. We greatly extend prior surveys of bile salt variation in fish and amphibians, particularly in analysis of the biliary bile salts of Agnatha and Chondrichthyes. While there is significant structural variation of bile salts across all fish orders, bile salt profiles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
152
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(161 citation statements)
references
References 61 publications
9
152
0
Order By: Relevance
“…Larval and adult lamprey are known to produce bile alcohol sulfates (26,28,43). Sulfation renders bile alcohols soluble, and enables their secretion.…”
Section: Resultsmentioning
confidence: 99%
“…Larval and adult lamprey are known to produce bile alcohol sulfates (26,28,43). Sulfation renders bile alcohols soluble, and enables their secretion.…”
Section: Resultsmentioning
confidence: 99%
“…The fatty acid levels in the blood are relatively low while the diet is lipid-rich (Plisetskaya, 1980), and, probably as in other Perciforms, the main bile components are phospholipids, cholic, and chenodeoxycholic acids along with 5b-bile alcohols (Moschetta et al, 2005;Hagey et al, 2010). Cholesterol nuclei could develop more easily from bile and cholecystocyte transport, because phospholipids appear generally absent in the bile of bony fish and most birds, while in mammals, the phospholipid to bile ratio varies widely among species.…”
Section: Discussionmentioning
confidence: 99%
“…strain Chol1 as a model organism. Bile salts are surface-active steroid compounds that are produced and released by vertebrates to aid the digestion of lipophilic nutrients (18)(19)(20); in addition, bile salts can also act as pheromones in some aquatic vertebrates (21,22). The characterization of two transposon mutants of strain Chol1, which are unable to grow with cholate, showed that the degradation of the C 5 acyl side chain of cholate proceeds via the stepwise removal of an acetyl and a propionyl residue.…”
mentioning
confidence: 99%